(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to know: 1- Cognitive complexity of educational counselors. 2- The significance of the differences in the cognitive complexity of educational counselors according to the gender variable (males – females). For the purpose of achieving the objectives of the current research, the researcher built a measure of cognitive complexity for educational counselors, which in its final form consisted of (20) paragraphs, after completing the conditions of honesty and stability and distinguishing the paragraphs. 70.7). The research is determined by the educational counselors in the directorates of education in the province of Baghdad for the academic year 2021/2020, and the research community consists of (1469) male and female counselors, amounting to (508) educational advisors and (961) educational counselors, and the research sample was chosen by random method, so the number of research sample members reached (400) As a guide, with (160) educational guides and (240) educational guides, the research relied on the descriptive associative approach. The results showed that educational counselors have: cognitive complexity, and males outperform females in cognitive complexity. According to the findings of the research, some recommendations and suggestions were presented.